2014
DOI: 10.1186/1471-2431-14-120
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atropine-sufentanil-atracurium anaesthesia for endotracheal intubation: an observational study in very premature infants

Abstract: BackgroundPremedication before neonatal intubation is heterogeneous and contentious. The combination of a short acting, rapid onset opioid with a muscle relaxant is considered suitable by many experts. The purpose of this study was to describe the tolerance and conditions of intubation following anaesthesia with atropine, sufentanil and atracurium in very premature infants.MethodsMonocentric, prospective observational study in premature infants born before 32 weeks of gestational age, hospitalised in the NICU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…1). Frequent blood gases and noninvasive CO 2 monitoring were needed to stabilize these infants along with escalating ventilation settings (pressures/change of ventilation modes) to optimize ventilation similar to the experience reported by Durrmeyer et al 3 They speculated that this might be secondary to the loss of lung recruitment during intubation resulting in decreased compliance and need for higher ventilator settings post muscle relaxant use. Based on this experience, our institution has moved away from using paralytics routinely in premature neonates as part of premedication.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…1). Frequent blood gases and noninvasive CO 2 monitoring were needed to stabilize these infants along with escalating ventilation settings (pressures/change of ventilation modes) to optimize ventilation similar to the experience reported by Durrmeyer et al 3 They speculated that this might be secondary to the loss of lung recruitment during intubation resulting in decreased compliance and need for higher ventilator settings post muscle relaxant use. Based on this experience, our institution has moved away from using paralytics routinely in premature neonates as part of premedication.…”
mentioning
confidence: 82%
“…2 We did not use a vagolytic agent as atropine may be associated with side effects in preterm infants with hypoxic bradycardia and can cause tachycardia in some neonates after intubation. 3,4 On implementation, we found that preterm infants had transient respiratory impairment requiring increased respiratory support immediately after using premedication. Data collected on premature infants (<34 weeks) who underwent elective (n ¼ 30, using premedication) and emergent intubation (n ¼ 26, without premedication) between 2013 and 2015 in our NICU are shown in ►Table 1.…”
mentioning
confidence: 99%
“…Laryngoscopy is undoubtedly uncomfortable, but when attempting LISA there is a better chance of achieving a success without sedation [67]. For planned non-urgent intubations, many clinicians prefer to use a combination of a short-acting opiate, muscle relaxant and atropine to maximise comfort [146] and improve chances of successful intubation [147]. Longer-acting muscle relaxants like vecuronium may increase the need for ventilation and should not be used [148].…”
Section: Pain and Sedationmentioning
confidence: 99%
“…Procedures such as venepuncture, intubation and MV all have potential to cause discomfort, and it is good practice to have mechanisms for evaluating pain using validated scoring systems [163]. Many clinicians prefer to use a combination of a short-acting opiate, muscle relaxant and atropine to maximize comfort and improve the chances of successful intubation [164]. However, there is a balance between ensuring comfort during laryngoscopy and not oversedating infants when trying to maintain them on non-invasive respiratory support [165].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%